2005
DOI: 10.2343/geochemj.39.289
|View full text |Cite
|
Sign up to set email alerts
|

Precise determination of REE for sedimentary reference rocks issued by the Geological Survey of Japan

Abstract: In order to obtain precise rare earth element (REE) compositions of sedimentary reference rocks issued by the Geological Survey of Japan (JSd-1, -2, JSl-1, -2, JLk-1), we analyzed their REEs by inductively-coupled plasma mass spectrometry (ICP-MS) using methods employing both acid digestion (HF-HClO 4 ) and carbonate fusion (Na 2 CO 3 -H 3 BO 3 ). Analytical precision of these methods was estimated by analyzing JB-1a and BCR-1 with the same procedure. Analyses of these two reference rocks show good reproducibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 18 publications
4
9
0
Order By: Relevance
“…As already noticed by Yamamoto et al (2005), compiled published values for JSd-1 and JSd-2 show clear deviations from smooth REE patterns, particularly within the HREE. We compared our results with those of Yamamoto et al (2005) who performed a two-step procedure using first an acid dissolution method followed by an alkali fusion method and a cation exchange column for REE separation. Our results are in very good agreement with their results and confirm the fact that compiled published values for HREE may not be the most reliable.…”
Section: Concentration/uccsupporting
confidence: 59%
See 1 more Smart Citation
“…As already noticed by Yamamoto et al (2005), compiled published values for JSd-1 and JSd-2 show clear deviations from smooth REE patterns, particularly within the HREE. We compared our results with those of Yamamoto et al (2005) who performed a two-step procedure using first an acid dissolution method followed by an alkali fusion method and a cation exchange column for REE separation. Our results are in very good agreement with their results and confirm the fact that compiled published values for HREE may not be the most reliable.…”
Section: Concentration/uccsupporting
confidence: 59%
“…This is particularly true for sediment samples, which are especially difficult to dissolve due to the occurrence of refractory minerals such as zircon. Numerous studies have been published, presenting various methods including conventional HF + HNO 3 acid dissolution procedures, HF + HNO 3 + HClO 4 procedures, with or without the use of high pressure digestion vessels or fusion techniques (Toutain and Meyer 1989, Makishima and Nakamura 1997, Townsend et al 1998, Yokoyama et al 1999, Liang et al 2000, Dulski 2001, Yu et al 2001, Taicheng et al 2002, Yamamoto et al 2005, Münker 1998. However, few studies have been specifically dedicated to sediment RMs and there is a need, therefore, for an efficient and reliable method for detrital sediment dissolution.…”
mentioning
confidence: 99%
“…Similar results have been observed in analysis of GSJ standards after carbonate fusion and acid digestion for precise determination of rare earth elements using ICP-MS [24]. Therefore, the aforementioned methods reported in literatures are not suitable for rapid and precise analysis of element concentrations in soils [11,24]. On the other hand, Mw-4 is an efficient rapid digestion method as explained in the present work and can be applied effectively to soil, sediment as well as rock samples of similar origin to JSd-2, JLk-1, JB-1 or JB-3.…”
Section: Comparison Between Digestion Methods For Jsd-2supporting
confidence: 83%
“…However, the recovery for some of the elements deviated from certified values (RB% > 20%). Similar results have been observed in analysis of GSJ standards after carbonate fusion and acid digestion for precise determination of rare earth elements using ICP-MS [24]. Therefore, the aforementioned methods reported in literatures are not suitable for rapid and precise analysis of element concentrations in soils [11,24].…”
Section: Comparison Between Digestion Methods For Jsd-2supporting
confidence: 67%
“…However, the existing results come from the surrounding area [3,4], and little study in the central Tibetan Plateau has been reported ( Figure 1). Previous studies have shown that, globally, the hottest period since the middle Pleistocene was at approximately 120 ka BP, which is recorded in the ice sheet above Lake Vostok in the Southern hemisphere [5] and in Greenland [6] in the Northern hemisphere. North Greenland Eemian Ice Drilling (NEEM) surface temperatures after the onset of the Eemian (126 ka) peaked at 8 ± 4°C above the mean of the past millennium [6].…”
Section: Introductionmentioning
confidence: 99%